2014
DOI: 10.1155/2014/479246
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Delivery Systems and Therapeutics of Cinnarizine: A Poorly Water Soluble Drug with Absorption Window in Stomach

Abstract: Low solubility causing low dissolution in gastrointestinal tract is the major problem for drugs meant for systemic action after oral administration, like cinnarizine. Pharmaceutical products of cinnarizine are commercialized globally as immediate release preparations presenting low absorption with low and erratic bioavailability. Approaches to enhance bioavailability are widely cited in the literature. An attempt has been made to review the bioavailability complications and clinical therapeutics of poorly wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 66 publications
1
24
0
2
Order By: Relevance
“…CDs have been used extensively for drug‐delivery applications because of their stability, biocompatibility, and ease of structural modification . Various studies have shown that CDs increase drug solubility and stability, contribute to sustained drug release, enhance membrane permeability and bioavailability, and minimize toxicity . As a result of these favorable properties and the ability of their hydroxyl groups to interact with iron oxide, many systems for targeted drug delivery, including IONPs, have incorporated CDs.…”
Section: Organic Macrocyclesmentioning
confidence: 99%
“…CDs have been used extensively for drug‐delivery applications because of their stability, biocompatibility, and ease of structural modification . Various studies have shown that CDs increase drug solubility and stability, contribute to sustained drug release, enhance membrane permeability and bioavailability, and minimize toxicity . As a result of these favorable properties and the ability of their hydroxyl groups to interact with iron oxide, many systems for targeted drug delivery, including IONPs, have incorporated CDs.…”
Section: Organic Macrocyclesmentioning
confidence: 99%
“…A large number of new chemical entities which have high potential to be developed as useful drugs have failed to reach the public merely due to the poor dissolution rate which results in unsatisfactory bioavailability. An orally administered drug must be insolubilized state and be able to cross the gastrointestinal tract (GIT) membrane to show its therapeutic effects [1]. The therapeutic effect of a drug relies on the bioavailability which is highly dependent on the solubility factor as well as the dissolution rate of the drug.…”
Section: Introductionmentioning
confidence: 99%
“…Основной группой лекарственныхпрепаратов, назначаемых при данной патологии, являются блокаторы кальциевых каналов,в частности циннаризин, эффективность которого доказана многочисленными клиническими исследованиями [5]. Существующие лекарственные формы цин-наризина имеют ряд недостатков, а именно: частота приема, наличие побочных эффектов [6,7]. Решением по нивелированию данных нежелательных факторов является разработка пролонгированной формы циннаризина, позволяющей уменьшить частоту приемов и тем самым избежать резких изменений концентрации препарата в организме, то есть способной поддерживать концентрацию препарата в организме относительно постоянной и терапевтический эффективной.…”
Section: Introductionunclassified